Analisis Fonemik Dan Sintaksis Pada Anak Usia 5-6 Tahun di TK Qurrota A’yun 01 Kota Pekalongan - Anna Diana Shanty; Anita Chandra Dewi (UIN Sultan Maulana Hasanudin Banten, 2021)
This study discusses the acquisition of phonemes and syntax in children aged 5-6 years, with a qualitative descriptive approach and tries to describe the phonemes and syntax of children who appear when reading a picture story book. The data mining carried out by researchers by observation, interviews and documentation. The results obtained 1) in the semantics of almost all children's utterances contain denotative meanings, there are also sentences that appear with connotative meanings, 2) children replace the sounds of several consonants, namely l and w with the aim of making it easier to pronounce. At the age of 5 years, the phonemes / o/ and / h / are released and there is a change in the phonemes / r / so / l /, /l/ becomes /w/, /g/ becomes d, /k/ becomes /t/, /nga / so / na/, / f/ becomes /p/, /s/ becomes / t/, /j/ becomes /d/, /z/ becomes / d/, /l/ becomes / w/. And there is also the release of some consonants in order to make it easier to pronounce such as / shampoo / become /tamas/. And for the syntax, children cannot identify the time of events such as today, tomorrow or yesterday. In stringing words into SPOK sentences, it still needs a lot of practice, especially exploring more children's vocabulary, practicing children to answer questions, of course educators using open sentences.